INFORMATION CULTURE AS A FACTOR FORMATION OF PEDAGOGICAL SKILLS - Volkova, N.V. (Pedagogy of Higher and Secondary Education, 2004)
The article deals with the problems of information culture, it shows factors that influence on the level of pédagogie skill.